Implementation of Qur’anic Verses on Multiculturalism in Project-Based Islamic Religious Education Learning at Elementary Schools: Implementasi Ayat Al-Qur’an tentang Multikulturalisme dalam Pembelajaran PAI Berbasis Proyek di Sekolah Dasar - Pitasari, Femi Dian; Murtadoilah, Hendi; Majdi, Muhamad (Medpro, 2025)
This article aims to examine the implementation of QS. Al-Baqarah verse 26 and QS. Ali Imran verse 64 in Islamic Religious Education (IRE) learning at the elementary school level through a Project-Based Learning (PjBL) approach to instill the values of multiculturalism. The study employed a qualitative descriptive method using literature review, observation, and interviews as data collection techniques. The findings indicate that PjBL-based IRE learning is effective in shaping students’ multicultural character, thereby making religious education more relevant and meaningful within its social context. This article recommends PjBL as a character education strategy that can strengthen tolerance and inclusivity in elementary schools. The PjBL approach was chosen because it enables students’ active engagement across cognitive, affective, and psychomotor domains through contextual and collaborative project activities. Its implementation is reflected in simple yet meaningful projects that foster cooperation, creativity, and value reflection, allowing students not only to understand the textual meaning of the verses but also to internalize moral messages of tolerance, dialogue, and peaceful coexistence in diversity. Furthermore, the school environment is utilized as a social laboratory that reinforces the learning of these values through cross-group social interactions. Thus, this study emphasizes that integrating Qur’anic values through PjBL can serve as a strategic model in religious education to cultivate a tolerant, inclusive generation prepared to live in a multicultural society.